Kepemimpinan dalam Administrasi Pendidikan - Sri Winarsih (UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2022)
Abstract Leadership is a force that moves a struggle or activity towards success. Leadership means the process of influencing group activities in the context of formulating and achieving organizational goals. Therefore, a leader must be able to optimize management and set a good example in office and in everyday life so that the organization becomes conducive and the quality of education increases. There are two things that characterize leaders in carrying out their duties, namely